Longitudinal assessment of von Willebrand factor antigen and von Willebrand factor propeptide in response to alteration of antiplatelet therapy after TIA or ischaemic stroke. - O'NEILL, DESMOND; MCCABE, DOMINICK; COUGHLAN, TARA (My University, 2014)
The impact of commencing or changing antiplatelet therapy on von Willebrand factor antigen (VWF:Ag) and von Willebrand factor propeptide (VWF:Ag II) levels has not been comprehensively assessed following TIA or ischaemic stroke. In this pilot, longitudinal, observational analytical study, VWF:Ag and VWF:Ag II levels were simultaneously quantified in platelet poor plasma by ELISA in patients within 4 weeks of TIA or ischaemic stroke (baseline), and then 14 days (14d) and >90 days (90d) after altering antiplatelet therapy. Ninety-one patients were recruited. Eighteen were initially assessed on no antiplatelet therapy, and then after 14d (N = 17) and 90d (N = 8) on aspirin monotherapy; 21 patients were assessed on aspirin and after 14d and 90d on clopidogrel; 52 were assessed on aspirin monotherapy, and after 14d and 90d on aspirin and dipyridamole combination therapy. VWF:Ag, VWF:Ag II levels and VWF:Ag/VWF:Ag II ratio were unchanged at 14d and 90d in the overall study population (p ≥ 0.1). VWF:Ag and VWF:Ag II levels remained stable at 14d and 90d after commencing aspirin (p ≥ 0.054), and after changing from aspirin to clopidogrel (p ≥ 0.2). Following the addition of dipyridamole MR to aspirin, there was a significant reduction in VWF:Ag levels at 14d (p = 0.03) and 90d (p = 0.005), but not in VWF:Ag II levels (p ≥ 0.3). The addition of dipyridamole to aspirin led to a persistent reduction in VWF:Ag but not in VWF:Ag II levels, suggesting that dipyridamole may inhibit release of platelet-derived VWF:Ag following TIA or ischaemic stroke.
PUBLISHED
Keywords: Stroke; Ageing; Neuroscience; Age related diseases